2022
DOI: 10.1021/acsomega.1c06226
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Metabolic Compositions and Trace Elements of Inonotus hispidus Mushroom Grown on Five Different Tree Species

Abstract: Inonotus hispidus is a popular edible and medicinal mushroom widely used in China. I. hispidus mushroom mainly grows on five different tree species ( Morus alba L., Ulmus macrocarpa Hance, Fraxinus mandshurica Rupr., Ziziphus jujuba Mill., and Malus pumila Mill.), and their fruiting bodies were all separately used in the market. However, there is no holistic insig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…On the other hand, some compounds not identified in previous works were iditol, hydroxyjasmonic acid sulfate (isomer 1 and 2), dihydrojasmonic acid sulfate, norwedelolactone, and hedysarimcoumestan F ( Table 3 ). The negative ionization pattern indicated that peak 1 was tentatively identified as iditol, with a molecular ion [M − H] − at m / z 181.0735, corresponding to the molecular formula C 6 H 14 O 6 , confirmed by characteristic ions ( m / z 163, 101, 89, 73, and 59), also detected in Inonotus hispidus mushroom [35] , and Daucus carota . In addition, Megías-Pérez et al [36] noted that the cocoa bean fermentation process is five to six days, and an extended time could lead to the development of undesirable molds.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, some compounds not identified in previous works were iditol, hydroxyjasmonic acid sulfate (isomer 1 and 2), dihydrojasmonic acid sulfate, norwedelolactone, and hedysarimcoumestan F ( Table 3 ). The negative ionization pattern indicated that peak 1 was tentatively identified as iditol, with a molecular ion [M − H] − at m / z 181.0735, corresponding to the molecular formula C 6 H 14 O 6 , confirmed by characteristic ions ( m / z 163, 101, 89, 73, and 59), also detected in Inonotus hispidus mushroom [35] , and Daucus carota . In addition, Megías-Pérez et al [36] noted that the cocoa bean fermentation process is five to six days, and an extended time could lead to the development of undesirable molds.…”
Section: Resultsmentioning
confidence: 99%
“…Metabolomics offers a comprehensive approach to elucidating the intricate chemical composition of G. lucidum [ 12 ]. Xia et al used a metabolomics approach and determined that ganoderic acid distribution was higher at the bottom of the cap mediostratum layer and in the stipe shell and context layers at the young bud stage, but did not reveal other material changes and molecular mechanisms [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, MA has been used as “ Sanghuang ” in both “The Ancient Course of the Yellow River” and southern Xinjiang regions. The types and enrichment degrees of chemical metabolites in the fruiting bodies of I. hispidus growing in five different tree species were reported to be significantly different using non-targeted metabolomics ( Li and Bao, 2022b ).…”
Section: Introductionmentioning
confidence: 99%